Development of prediction models of COVID-19 vaccine uptake among Lebanese and Syrians in a district of Beirut, Lebanon: a population-based study - Hala Ghattas; Jocelyn Dejong; Fadi El-Jardali; Stephen J McCall; Marie-Elizabeth Ragi; Aline Germani; Hazar Shamas; Nada M Melhem (BMJ Publishing Group, 2024)
Introduction Vaccines are essential to prevent infection and reduce the morbidity of infectious diseases. Previous evidence has shown that migrants and refugees are particularly vulnerable to exclusion and discrimination, and low COVID-19 vaccine intention and uptake were observed among refugees globally. This study aimed to develop and internally validate prediction models of COVID-19 vaccine uptake by nationality.Methods This is a nested prognostic population-based cross-sectional analysis. Data were collected between June and October 2022 in Sin-El-Fil, a district of Beirut, Lebanon. The study population included a random sample of Lebanese adults and all Syrian adults residing in areas of low socioeconomic status. Data were collected through a telephone survey. The main outcome was the uptake of at least one dose of the COVID-19 vaccine. Predictors of COVID-19 vaccine uptake were assessed using the Least Absolute Shrinkage and Selection Operator regression for Lebanese and Syrian nationalities in separate models.Results Of 2028 participants, 79% were Lebanese, 18% Syrians and 3% of other nationalities. COVID-19 vaccination uptake was higher among Lebanese (85% (95% CI 82% to 86%) compared to Syrians (47% (95% CI 43% to 51%)) (p<0.001); adjusted OR 6.2 (95% CI 4.9 to 7.7). Predictors of uptake of one or more COVID-19 vaccine doses for Lebanese were older age, presence of an older adult in the household, higher education, greater asset-based wealth index, private healthcare coverage, feeling susceptible to COVID-19, belief in the safety and efficacy of vaccines and previous receipt of the influenza vaccine. For Syrians, predictors were older age, male sex, completing school or higher education, receipt of cash assistance, presence of chronic illness, belief in the safety and efficacy of vaccines, previous receipt of the influenza vaccine and possession of a legal residency permit in Lebanon.Conclusions These findings indicate barriers to vaccine uptake among Syrian refugees and migrants, including legal residency status. These findings call for urgent action to enable equitable access to vaccines by raising awareness about the importance of vaccination and the targeting of migrant and refugee populations through vaccination campaigns.